2013
DOI: 10.4028/www.scientific.net/amr.660.19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Poly(N-vinlycarbazole) Blending with Different Composition by Using Polarized Electronic Spectroscopy

Abstract: Polarized absorption and dielectric spectra of blended poly (N-vinlycarbazole) (PVK) with polyvinylpyrrolidone (PVP) in different composition ratiosare investigated. Polymer coating was carried out using doctor blade technique on a quartz substrate. The polarized optical source was produced by using the uv-vis sheet polarizer. The polarized absorption and dielectric spectrum for parallel and perpendicular reveal that there are different significant results obtained between PVK and PVP with various polymer comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Optical characterizations of polymers are vital tools for understanding the electronic properties of polymers [5]. Optical absorption and luminescence spectroscopy rely on electron transition from the * corresponding author; e-mail: ahmadnazib111@ppinang.uitm.edu.my highest occupied molecular orbital to the lowest unoccupied molecular orbital or on the nonlinear optical properties of a polymeric material.…”
Section: Introductionmentioning
confidence: 99%
“…Optical characterizations of polymers are vital tools for understanding the electronic properties of polymers [5]. Optical absorption and luminescence spectroscopy rely on electron transition from the * corresponding author; e-mail: ahmadnazib111@ppinang.uitm.edu.my highest occupied molecular orbital to the lowest unoccupied molecular orbital or on the nonlinear optical properties of a polymeric material.…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that the value of the refractive index increases with the increase of MoO3 concentration especially at low wavelength region. This type of composite film has a high refractive index which makes it possible to use it in wave guide technology, antireflective coating and photonic devices [25]. 5.…”
Section: Resultsmentioning
confidence: 99%
“…There are many benefits of polymers, for example, low cost, fast treatment, durability, strong high strength and mechanical properties. They are used in the photolithography process in the microelectronic fabrication industry [18][19][20]. Polymeric nanocomposites consisting of inorganic nanoparticles and organic polymers constitute a class of materials, which, in recent years, have created considerable interest [21].…”
Section: Polymer Nanocompositesmentioning
confidence: 99%